PERKEMBANGAN USIA DINI (AWAL MASA KANAK KANAK): PERKEMBANGAN KEPRIBADIAN, BERMAIN PADA MASA USIA DINI, RESIKO (BAHAYA) DAN IMPLIKASI DALAM LAYANAN KONSELING - Mitha Rafina; Siti Fatimah; Suci Amelia (JURNAL ILMIAH RESEARCH STUDENT, 2023)
Early childhood is a period of development from 2-6 years of age. Children at this time like to explore and have an egocentric attitude where they always see everything from their own perspective. Early childhood is also called the aesthetic and sensory period, because this is the time when children's feelings of beauty and sensory development develop rapidly. The research uses the critical review method by reading various books, journals or other publications related to the research topic discussed. The journals chosen consist of national and international journals, as well as several official websites. Research using this method is carried out by comparing research methods, processing methods, and the results obtained from each article. The research source comes from articles obtained via the internet in the form of research articles discussing early childhood development. The research results are as follows; a) Personality development, Personality is a self-concept. As the self-concept is the basic pattern of personality. b) Playing, Playing is one of the main tools that provides training for children's growth and development. c) Danger, there are physical and psychological dangers. d) Implications, Implications are the direct consequences or consequences of certain final results.